Sosialisasi dan Pelatihan Pembuatan Pupuk Organik Cair (POC) di Pondok Pesantren Al-Azhaar Tulungagung dari Limbah Air Cucian Beras - Rohmatul Faizah; Nur Aini Mahfud; Nur Qomariyah Deviyanti; Ekafianda Azzhara Suprapto; Nurdiah Khasanah; Dwi Rosa Ilma Silfia; Risa Lukestiana (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Rice washing water is one of the household wastes that has the potential to be utilized. Research shows that rice washing water can be useful as a Liquid Organic Fertilizer (POC) which can be used as a plant fertilizer and soil fertilizer. Nutrients from rice washing water are processed into POC in the form of N, P, and K and other microelements obtained from the results of fermentation carried out for some time. POC from rice washing water waste also provides real benefits to plant growth, increases fruit weight and number of leaves. The purpose of conducting socialization and training on making POC from rice washing water waste at the Al Batul Tulungagung cottage is for female students to be able to process rice washing water waste which was initially useless so that it can be utilized into a more useful product in the form of liquid organic fertilizer.